2020
DOI: 10.4067/s0717-95022020000100159
|View full text |Cite
|
Sign up to set email alerts
|

Tubérculo Marginal del Hueso Cigomático

Abstract: RESUMEN: El hueso cigomático, ubicado en la parte superior y lateral de la cara, es un hueso par e irregular con forma cuadrilátera o romboidal. Se describen 2 caras, 4 aristas y 4 ángulos, forma cavidades, permite la inserción muscular y aponeurótica, es parte de la arquitectura facial, distribuye las fuerzas masticatorias y permite el paso del nervio cigomático. Su margen postero-superior presenta una prominencia ósea conocida como tubérculo marginal, en el que se observa la inserción de la fascia temporal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…MW, therefore, wanted to test whether this was indeed a sexually dimorphic feature that can be used as a sex indicator. Silva et al (2020), in a study on Chilean skulls, found that the tubercle was indeed more prominent in males than females.…”
Section: Method: Selected Skull Featuresmentioning
confidence: 94%
“…MW, therefore, wanted to test whether this was indeed a sexually dimorphic feature that can be used as a sex indicator. Silva et al (2020), in a study on Chilean skulls, found that the tubercle was indeed more prominent in males than females.…”
Section: Method: Selected Skull Featuresmentioning
confidence: 94%